Регулювання православною церквою шлюбно-сімейних відносин (на прикладі Південної України останньої чверті XVIII ст.) (Zaporizhzhia Historical Review, 2021)
The role of Orthodox Church in marriage-family relations in Russian empire on the example of South Ukrainian in the end of 18-th century is analyzed in the article. The author tries to prove that customary law was gradually dying because of strengthening of the role of autocracy and Orthodox Church in the South Ukraine. Marriages, divorces and otherdirections of marriage-family relations became the competence of church authority, were regulated and sanctified by Church.